BİZANS İMPARATORLUĞU'NDA SARAY TEŞKİLATI - ATAŞ, ZİLHACE (Fırat Üniveristesi, 2007)
Saray, hükümdarın oturdugu büyük bina olmanın yanı sıra yönetimin merkezi olması açısından önem tasır. Bizans mparatorlugu'nda saraylar mimari olarak büyük ve gösterisli binalardı. Bu büyüklük ve gösteris Bizans'ın gücünü temsil ediyordu. Romanın daha çok Sasani ? ran saraylarından etkilenerek yaptırdıgı büyük ve gösterisli saraylar, Bizans mparatorlugu'na miras kalmıs ve Bizans da bu mirasın hakkını vererek çok daha büyük ve gösterisli saraylar meydana getirmistir. Konstantinopolis'in kurulusundan itibaren genel olarak XII. yüzyıla kadar imparatorlar Büyük Saray'da oturmus ve devleti buradan yönetmislerdi. XII. yüzyıldan sonra yeni saraylar yapılmıs ve bu saraylar imparatorlugun merkezi olmustur. Yeni yapılan saraylar da gösteris ve ihtisam yönünden Büyük Saray'dan geri kalmayacak güzellikte ve büyüklükte insa edilmistir. Sonuç olarak Bizans sarayları, gerek imparator ve ailesinin oturdugu malikane olması gerekse de yönetimin merkezi olması sebebiyle incelenmeye degerdir

Palace was not only big structure that emperor were living in, it was also important because palace was c:[entre of the management. The meaning with the palace was to attract attention to the power of the Byzantine trough both palaces beautiful appearance and the architecture. The power of Byzantine was comparing with the palaces size. How big and imposing palace was, Byzantine was as much as strong and powerful and the empire would be able to manage to the others. All those big and imposing palaces who built under Roma period were mostly inspired by Sassanid ? Iran?s palaces and they were handed down from Roma to Byzantine Empire. Byzantine Empire successfully continued to build bigger and more imposing palaces. Since foundation of Constantinople which was succession of Roma, until XII century Great Palace was imperial residence and emperors was administering country from here. After XII century new palaces were built and they became a centre of management. New palaces were in no way inferior to the Great Palace. As a result Byzantine Palaces are still fascinating and a theme of many investigation and research by being both imperial residence and having a wonderful architecture.
Palace organization in the Byzantine Empire
Keywords: Tarih